Numerical assessment of heat transfer and mixing quality of a hybrid nanofluid in a microchannel equipped with a dual mixer - Pouya Barnoon (Elsevier, 2021)
The present study investigates the electroosmotic flow and heat transfer of a hybrid nanofluid within a microchannel equipped with a dual mixer by presenting a new design. Four pairs of electrodes are mounted on the mixers, which can increase the mass diffusion by absorbing ions into the electrodes and generate vortices. The hybrid nanofluid contains silver (Ag) and iron oxide (Fe3O4) nanoparticles based on pure water that is injected into the microchannel in different volume fractions. The numerical results show that when heat fluxes are applied to the cores, the use of all-insulated microchannels significantly increases the microchannel temperature and cannot produce the desired results. Therefore, an idea to control the microchannel temperature and increase heat transfer is proposed. Increasing the frequency and electric potential can enhance the mixing quality. A specific frequency is proposed for each Reynolds number at different times. The results show that the best mixing quality is 87.5%, which can be achieved at a minimum flow rate and 0.5 seconds. Using the hybrid nanofluid in a volume fraction of 1.4%, the heat transfer can be increased to 7.29% compared to the pure fluid. The results show that from 0.015 seconds onwards, the heat transfer inside the microchannel reaches an almost stable state. Reducing the Reynolds number and increasing the frequency play an essential role in improving the mixing quality.